Sistem Informasi Penempatan Pegawai Terhadap Kinerja Pegawai di Dinas Pendidikan Kota Tanjung Balai - Rafi Alifian Fayadh (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This report discusses the development of an employee placement information system to enhance employee performance at the Tanjungbalai City Education Office. With the advancement of information technology, proper employee placement based on qualifications and competencies has become a crucial factor in organizational efficiency. This study employs the Multifactor Evaluation Process (MFEP) method to objectively evaluate employee placement. The developed system is web-based to facilitate access and processing of employee performance evaluation data. The findings indicate that this system assists decision-making in optimizing employee placement, improving work effectiveness, and providing recommendations for employee performance evaluation.